2013
DOI: 10.1007/s12035-013-8556-x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 EP1 Receptor Antagonist Improves Motor Deficits and Rescues Memory Decline in R6/1 Mouse Model of Huntington's Disease

Abstract: In this study, we evaluated the potential beneficial effects of antagonizing prostaglandin E2 (PGE2) EP1 receptor on motor and memory deficits in Huntington's disease (HD). To this aim, we implanted an osmotic mini-pump system to chronically administrate an EP1 receptor antagonist (SC-51089) in the R6/1 mouse model of HD, from 13 to 18 weeks of age, and used different paradigms to assess motor and memory function. SC-51089 administration ameliorated motor coordination and balance dysfunction in R6/1 mice as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
4
32
1
Order By: Relevance
“…Moreover, using a mouse model of cerebral ischemia and Alzheimer’s disease, we have shown that EP1 receptor blockade could be beneficial for treatment of both conditions [33]. In addition, recent data from another group indicate that the EP1 receptor antagonist used in our study demonstrated strong a therapeutic effect of repeated treatments with SC-51089 (40 µg/kg) in a murine model of Huntington’s disease and pointed out this compound as a new therapeutic candidate for motor and cognitive deficits characteristic for this and other neurodegenerative disorders [40]. Our previous preclinical data also suggested potential therapeutic applications of the antagonists of prostaglandin F 2α FP receptor, which exerts Ca 2+ -modulating effects similar to the EP1 receptor in ischemic stroke and TBI, and these data indicate that despite considerable differences between the mechanisms of primary injury in these models, beneficial effects were obtained with similar treatment regimens [18], [20], [21].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Moreover, using a mouse model of cerebral ischemia and Alzheimer’s disease, we have shown that EP1 receptor blockade could be beneficial for treatment of both conditions [33]. In addition, recent data from another group indicate that the EP1 receptor antagonist used in our study demonstrated strong a therapeutic effect of repeated treatments with SC-51089 (40 µg/kg) in a murine model of Huntington’s disease and pointed out this compound as a new therapeutic candidate for motor and cognitive deficits characteristic for this and other neurodegenerative disorders [40]. Our previous preclinical data also suggested potential therapeutic applications of the antagonists of prostaglandin F 2α FP receptor, which exerts Ca 2+ -modulating effects similar to the EP1 receptor in ischemic stroke and TBI, and these data indicate that despite considerable differences between the mechanisms of primary injury in these models, beneficial effects were obtained with similar treatment regimens [18], [20], [21].…”
Section: Discussionsupporting
confidence: 64%
“…To overcome the possibility of nonoptimal timing or low dose due to lack of the pharmacokinetic and bioavailability data, in this study, all TBI outcomes measured in WT mice were compared with those obtained in EP1 −/− mice, and all drug treatment experiments performed in WT mice were replicated in EP −/− mice. The lack of effects of the EP1 receptor pharmacological blockade or knockout on either neurobehavioral and anatomical outcomes or Iba1 and GFAP immunohistochemistry in our in vivo CCI model of TBI, which is in contrast with the neuroprotective effects observed in the related in vitro studies [18], [34] and the in vivo models of ischemia and excitotoxicity [19], [22], [23], [40], suggests that involvement of other cell types expressing the EP1 receptor contribute considerably to the brain pathology following TBI. Our data is consistent in part with a report demonstrating a lack of the protective effects of pretreatment with EP1 receptor inhibition in a model of blade incisions leading to localized surgical brain extraction followed by electrocautery by Dr. J. H. Zhang’s group [25].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Presynaptic expression of VGluT1 contributes to the proper expression of other synaptic proteins and reduced levels of this glutamate transporter, as occurs in the striatum of R6 mice [154,155], can disrupt cortico-striatal synaptic transmission [154,156]. The expression of glutamate transporters is also altered in glial cells.…”
Section: Glutamate Transportersmentioning
confidence: 99%